Management of kidney cancer patients: 2018 guidelines of the Italian Medical Oncology Association (AIOM). Issue 4 (July 2019) - Giuseppa Vitale, Maria; Bracarda, Sergio; Cosmai, Laura; Crocetti, Emanuele; Di Lorenzo, Giuseppe; Lapini, Alberto; Mandressi, Alberto; Martorana, Giuseppe; Masini, Cristina; Montironi, Rodolfo; Ortega, Cinzia; Passalacqua, Rodolfo; et al.
In the past two decades, the treatment landscape for patients with metastatic renal cell carcinoma has significantly changed thanks to the approval of several targeted molecular therapies (VEGF and mTOR inhibitors) and recently immune-checkpoint inhibitors. The Italian Association of Medical Oncology (AIOM) Renal Cell Cancer (RCC) Guidelines Panel has developed clinical guidelines to provide evidence-based information and recommendations to oncologists, urologists and all professionals involved in the management of patients with renal cell cancer.